The International Space Station - Morey, Allan (Minneapolis, MN : Bellwether Media, Inc., 2018)
"Engaging images accompany information about the International Space Station. The combination of high-interest subject matter and light text is intended for students in grades 2 through 7"--
Includes bibliographical references and index.
Age 7-12.
Grades 2-7.
Keywords: International Space Station -- Juvenile literature; Space stations -- Juvenile literature